(untitled) (INNOTEC, 2012)
The use of renewable energies is of increasing importance due to depletion of fossil fuel sources and environmental damages caused by their utilization. The energy available from the sun is clean and widely distributed. Solar cells are devices used to convert solar energy into electricity. Among them, dye sensitized solar cells are an interesting alternative to conventional silicon ones, because of their low cost and simple assembly process. They are made of a semiconductor with colored dyes adsorbed onto the surface that work as antennas to catch energy in the visible range of the spectra. In this work, nanostructured TiO2 was synthesized and the protein phycocyanin was used as dye. TiO2 was characterized by electron microscopy, X ray diffraction and infrared spectroscopy (FTIR). Phycocyanin was extracted from commercial Spirulina spp. capsules. The assembly process of the electrode covered with TiO2 and phycocyanin was controlled by cyclic voltammetry and FTIR. Results were in accordance with the assembling of an electrode sensitized with phycocyanin.